The public perception of adopting hydrogen fuel cell vehicles in Kuala Lumpur, Malaysia - Rusinah Siron,; Saraswathy Kasavan,; Amar Hisham Jaaffar, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Hydrogen fuel cell vehicles (HFCV) are leading as alternative energy-saving vehicles that replace non-renewable energy use and support sustainable transport systems for developing and developed countries. Public adoption of new transport technologies is vital for the successful evolution of a sustainable energy system. Previous studies have focused more on people’s attitudes towards hydrogen energy as alternative fuel energy. This article aims to assess the public perception of the adoption of HFCV in Kuala Lumpur, Malaysia. The overall results of this study found that demand-side action for HFCV among the public is influenced by supply-side aspects, including support infrastructure, characteristics of HFCV, operational costs, safety concerns, competitive markets, and the social equilibrium of the innovation. The current study also found that most respondents have a scant idea of the environmental benefits of using HFCV. The evidence from this study suggests that stakeholders should educate the public regarding the benefits of HFCV - an essential step when adopting new technologies. It is timely to seek innovative solutions and address appropriate policies for both energy security and environmental concerns globally in the transportation sector for the sake of present and future sustainability.